The effect of heating method on the gel structures and properties of surimi prepared from Bombay duck (Harpadon nehereus) - Li, Mingao; Yang, Jing; Bao, Hongli; Chen, Yi; Gao, Yuanpei; Deng, Shanggui (Frontiers in Nutrition, 2022)
This study investigates the effects of heating method, setting time, and setting temperature on the gel properties, water holding capacity (WHC), molecular forces, protein composition, protein conformation, and water transition of Bombay duck (BD) surimi gel. The obtained results demonstrate that the best gel properties are obtained by two-step heating at 30°C for 120 min while the hardness was 10.418 N and the breaking force was 4.52 N. Gel softening occurs at setting temperatures greater than 40°C due to the effect of endogenous enzymes in destroying the protein structure and increasing the hydrophobic and disulfide interactions. Low-field nuclear magnetic resonance spectra confirm that high two-step setting temperatures induce gel softening and the destruction of the surimi gel structure, as evidenced by the increased water migration at these temperatures. Of all protein conformations in the gel, the β-sheet structure, decreases from 38.40% at 30°C to 11.75% at 60°C when the setting time is 60 min, is the most susceptible to gel softening. Overall, the data reported herein provide a scientific basis for the development of new BD surimi products on an industrial level.